Euryale Ferox Seed‐Inspired Superlubricated Nanoparticles for Treatment of Osteoarthritis. (2nd December 2018) - Yan, Yufei; Sun, Tao; Zhang, Hongbo; Ji, Xiuling; Sun, Yulong; Zhao, Xin; Deng, Lianfu; Qi, Jin; Cui, Wenguo; Santos, Hélder A.; Zhang, Hongyu
Abstract: Osteoarthritis has been regarded as a typical lubrication deficiency related joint disease, which is characterized by the breakdown of articular cartilage at the joint surface and the inflammation of the joint capsule. Here, inspired by the structure of the fresh euryale ferox seed that possesses a slippery aril and a hard coat containing starchy kernel, a novel superlubricated nanoparticle, namely poly (3‐sulfopropyl methacrylate potassium salt)‐grafted mesoporous silica nanoparticles (MSNs‐NH2 @PSPMK), is biomimicked and synthesized via a one‐step photopolymerization method. The nanoparticles are endowed with enhanced lubrication by the grafted PSPMK polyelectrolyte polymer due to the formation of tenacious hydration layers surrounding the negative charges, and simultaneously are featured with effective drug loading and release behavior as a result of the sufficient mesoporous channels in the MSNs. When encapsulated with an anti‐inflammatory drug diclofenac sodium (DS), the lubrication capability of the superlubricated nanoparticles is improved, while the drug release rate is sustained by increasing the thickness of PSPMK layer, which is simply achieved via adjustment of the precursor monomer concentration in the photopolymerization process. Additionally, the in vitro and in vivo experimental results show that the DS‐loaded MSNs‐NH2 @PSPMK nanoparticles effectively protect the chondrocytes from degeneration, and thus, inhibit the development of osteoarthritis. Abstract : Bioinspired by the unique structure of the fresh euryale ferox seed, a novel superlubricated drug‐loaded nanoparticle is designed and synthesized based on photopolymerization for the treatment of osteoarthritis.